Rectal Cancer Risk After Colectomy in Patients With Inflammatory Bowel Disease—A Population-Based Danish Cohort Study 1978–2018 - Elena Akimenko; Jacob Tveiten Bjerrum; Aske Thorn Iversen; Kristine H. Allin; Tine Jess (Gastro Hep Advances, 2023)
Background and Aims: Selected patient groups with ulcerative colitis and Crohn's disease are at increased risk of colorectal cancer. Surveillance guidelines rarely cover patients after colectomy. We performed a nationwide population-based cohort study to estimate the risk of developing rectal cancer in patients with inflammatory bowel disease after subtotal colectomy. Methods: Through the Danish Civil Registration System, a source population of all individuals living in Denmark between 1978 and 2018 was retrieved. The risk of rectal cancer in patients with diverted rectum was assessed using Cox regression analyses with comparison to both the individuals with inflammatory bowel diseases without subtotal colectomy and the background population. Results: Rectal cancer occurred in 42 of 4931 patients (0.9%) after subtotal colectomy and diverted rectum, compared to 209 of 49,251 (0.4%) in the matched inflammatory bowel diseases cohort without colectomy and 941 of 246,550 (0.4%) in the background population. The hazard ratio (HR) for rectal cancer in patients with inflammatory bowel disease and diverted rectum vs patients without colectomy was 0.76 (95% CI, 0.28, 2.07) before 10 years and 7.56 (95% CI, 5.21, 10.86) 10 years after colectomy. The HR for patients with diverted rectum compared to the background population was 0.84 (95% CI, 0.31, 2.24) and 10.01 (95% CI, 7.20, 13.94) respectively. Conclusion: In our nationwide population-based Danish cohort study, we found the risk of rectal cancer in the diverted rectum to be markedly increased 10 years postcolectomy. This calls for better long-term surveillance of colectomized patients with inflammatory bowel diseases.